Study of postpartum amenorrhea in Uttar Pradesh using Exponential distribution for NFHS-5 data - Ravi Kant Maurya; Raman Pant; Anil Kumar; Soni, Ridhima (Brazilian Journal of Biometrics, 2025)
Postpartum amenorrhea (PPA) is a very crucial biological phenomenon in women. Besides this, it is also influenced by various socioeconomic determinants. PPA indicates the duration of infecundity among women after childbirth and resumption of ovulation. In this study, the exponential distribution has been fitted to four randomly selected districts of Uttar Pradesh. Data has been taken from the fifth round of the National Family Health Survey. The effect of demographic factors on the PPA of each selected district was analyzed along with education, caste, body mass index (BMI), and wealth index. The findings of this study indicate that in Varanasi the maximum percentage of women in the 0-5 months int erval, who have completed secondary education, belong to the OBC category, have normal BMI, and are from the richer and richest category. In Gazipur most women’s PPA duration was between 0 to 5 months, and most of them are from the other backward classes c ategory and have completed their secondary education, have normal BMI, and are from the poorest to middle category. In Jaunpur the maximum percentage of women lies in the 0-5 months interval, who have completed secondary education, belong to the OBC category, have normal BMI, and are from the poorer to middle category. In Bhadohi most women’s PPA duration was between 0 to 5 months, and most of them are from the other backward classes category and have completed their secondary education, have normal BMI, an d are from the poorer to poorest category. All the districts are similar according to distribution and we found that exponential distribution is the theoretical distribution for PPA data of selected districts of Uttar Pradesh.